2021
DOI: 10.21468/scipostphys.10.2.049
|View full text |Cite
|
Sign up to set email alerts
|

Floquet conformal field theories with generally deformed Hamiltonians

Abstract: In this work, we study non-equilibrium dynamics in Floquet conformal field theories (CFTs) in 1+1D, in which the driving Hamiltonian involves the energy-momentum density spatially modulated by an arbitrary smooth function. This generalizes earlier work which was restricted to the sine-square deformed type of Floquet Hamiltonians, operating within a \mathfrak{sl}_2𝔰𝔩2 sub-algebra. Here we show remarkably that the problem remains soluble in this generalized case which involves the full Virasoro algebra, based … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 66 publications
(146 reference statements)
1
49
0
Order By: Relevance
“…In contrast, it shows an oscillatory behavior in the non-heating phase and a logarithmic growth on the phase boundary. Finally, we would like to point out that all of these studies focussed on evolution starting from the CFT vacuum on a strip geometry [32][33][34][35][36][37][38]; the dynamics of the system starting from asymptotic states corresponding to primary operators of the theory, which necessitates computation of four-point correlation functions of the primary fields of the driven CFT, has not been studied so far. This is one of the main goals of this work.…”
Section: Jhep05(2021)172mentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, it shows an oscillatory behavior in the non-heating phase and a logarithmic growth on the phase boundary. Finally, we would like to point out that all of these studies focussed on evolution starting from the CFT vacuum on a strip geometry [32][33][34][35][36][37][38]; the dynamics of the system starting from asymptotic states corresponding to primary operators of the theory, which necessitates computation of four-point correlation functions of the primary fields of the driven CFT, has not been studied so far. This is one of the main goals of this work.…”
Section: Jhep05(2021)172mentioning
confidence: 99%
“…The exact solution for U (T, 0) for Hamiltonians valued in su (1,1) and driven by discrete protocols were discussed earlier for periodic kicks [46] and square pulse protocols [32][33][34][35][36][37][38]. It was found that such driven system could display two distinct phases depending on the drive parameters; these are termed as the heating (hyperbolic) and the non-heating (elliptic) phase and are found to be separated by a transition line (parabolic phase boundary) [46].…”
Section: Jhep05(2021)172mentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, the Möbius and SSD Hamiltonians have been used to study non-equilibrium processes. In particular, in (1+1)d CFT, solvable models of quantum quench [58] and Floquet dynamics [59,60,61,62,63,64,65] can be constructed using the Möbius and SSD Hamiltonians. They provide rare examples where the dynamics of interacting many-body quantum systems can be solved analytically.…”
Section: The Möbius and Ssd Hamiltoniansmentioning
confidence: 99%